Evidence of dynamic visual acuity impairment in asymptomatic mixed martial arts fighters. (7th July 2017) - Landers, Merrill R; Donatelli, Robert; Nash, Jennifer; Bascharon, Randa
Aim: The purpose of this study was to determine the amount of visual acuity loss with head movement in actively training mixed martial arts (MMA) fighters.Methods: Vestibulo-ocular reflex function of 22 asymptomatic, male MMA fighters (age = 29.2 ± 5.1) was assessed by taking the difference between static visual acuity and the dynamic visual acuity test, in both yaw and pitch planes.Results: The mean static visual acuity testing logMAR was -0.173 (standard deviation [SD] = 0.114). Mean dynamic visual acuity test values decreased with head movement to 0.196 logMAR (SD = 0.103) in yaw; p < 0.001, and to 0.283 logMAR (SD = 0.133) in pitch; p < 0.001.Conclusion: MMA fighters had a decay, beyond normal ranges, in visual acuity during head movement. These decreases may suggest vestibulo-ocular reflex impairment and were unrelated to self-reported concussion history. These results should be cautiously interpreted since there was not a control group.